ANALISIS YURIDIS TERHADAP ALAT BUKTI VISUM ET REPERTUM PSIKIATRIKUM DALAM KASUS TINDAK PIDANA PERKOSAAN (STUDI KASUS PUTUSAN PENGADILAN TINGGI BANJARMASIN NOMOR 42/PID/2017/PT BJM) - Yitro Daniel; Dian Adriawan Dg Tawang (Jurnal Hukum Adigama, 2019)
Based on Decision Number 20 / Pid.B / 2017 PN.Mrh has reported rape issued by the wife of Suwito Budi Santoso while the wife of Suwito Budi Santoso is named Sumaryati. However, Decision Number 42 / PID / 2017 / PT.BJM, the Banjarmasin High Court Judge Council acquitted 7 defendants who were not proven in rape cases. However, in the court's ruling, the Banjarmasin High Court contained anomalies that differed from the Verdict of the Marbahan District Court, namely from the expert's statement and the results of the post mortem psychiatric review. The problem is how is the juridical analysis of the evidence evidence and psychiatric repertum in the case of rape (case study of the Decision of the High Court in banjaran 42 / PID / 2017 / PT BJM)? The author approves this problem using normative research methods supported by expert interview data. The author creates in Article 184 the Criminal Procedure Code valid evidence is divided into 5 (five), which consists of legal evidence categorized Letters which are translated Article 187 and in Perma No 3 of 2017 in Article 4 to be discussed by the Judge. The author asks that for Law Enforcement, to pay more attention to what matters are the contents of the legislation. Investigators, Public Prosecutors, Judges, and government institutions that are involved in the tools of the post mortem and psychiatric repertum in the crime of rape, must really realize the contents of the agreement. So that the legal certainty given by the State to the community can be fully accepted